Responsible Artificial Intelligence Adoption and Employee Innovative Behavior in the Service Industry: A PLS-SEM Mediation Analysis of Psychological Empowerment - Kofi Mensah (Kalam Practica Media, 2026)
This study examines the influence of Responsible Artificial Intelligence Adoption on Employee Innovative Behavior by investigating the mediating role of Psychological Empowerment within service organizations. A cross-sectional quantitative research design was employed using data collected from 485 employees working in the service sector. The proposed research model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) implemented in SmartPLS 4. Measurement model reliability and validity were evaluated prior to testing the structural relationships, while hypothesis testing was conducted using a bootstrapping procedure with 5,000 resamples. The empirical findings indicate that Responsible Artificial Intelligence Adoption exerts a significant positive effect on Psychological Empowerment (β = 0.584, p < 0.001) and Employee Innovative Behavior (β = 0.412, p < 0.001). Psychological Empowerment also serves as a significant partial mediator between Responsible Artificial Intelligence Adoption and Employee Innovative Behavior, with a statistically significant indirect effect (β = 0.298, p < 0.001). Furthermore, the proposed model demonstrated satisfactory predictive capability and model fit, with a predictive relevance value (Q²) exceeding 0.35, a Standardized Root Mean Square Residual (SRMR) of 0.052, and a Normed Fit Index (NFI) of 0.912. These findings suggest that the successful implementation of responsible and transparent artificial intelligence systems extends beyond technological efficiency by strengthening employees' psychological empowerment. When AI technologies are perceived as ethical, transparent, and supportive rather than controlling, employees experience greater autonomy, competence, and meaningfulness in their work. These psychological conditions encourage higher levels of creativity and innovative behavior, enabling service organizations to leverage responsible AI as a strategic resource for enhancing workforce innovation and sustaining organizational competitiveness.